Wise Socialization In Use Technology And Information: Sosialisasi Bijak Dalam Menggunakan Teknologi Dan Informasi - Emi handrina; Gusnayetti (Journal of Community Service and Application of Science, 2023)
This Community Service project aims to provide smart and wise socialization in using technology and information, as it can have a significant positive impact on the development and application of science in society. The project is entitled "Smart and Wise Socialization in Using Technology and Information" and is specifically targeted towards the environment of  SMAN 6 Solok Selatan, located in Solok Selatan. The primary method employed by students in this project community is the problem-solving method, which involves delivering material first to ensure that students understand the more productive ways of using technology. This method also emphasizes the importance of maintaining data privacy and provides guidance on how to do so. Furthermore, the implementation of each point is demonstrated, followed by a question-and-answer discussion session to address any queries related to the material that has been presented. Through this community service, tertiary institutions can contribute to the promotion of smart and wise use of information technology in society